Formulation Development and Characterization of Levosalbutamol Sulphate Oral Thin Film using Propylene glycol as a Plasticizer - Morshed, Md Masud; Mallick, Jewel; Islam, Fahamida; Islam, Md Kamrul; Sohel, Md Didaruzzaman; Kawsar, Md Hassan (Bangladesh Pharmaceutical Journal, 2017)
The present study was concerned with the preparation and evaluation of oral thin films of levosalbutamol sulphate (LS) is to avoid presystemic elimination by gastrointestinal degradation and first pass hepatic metabolism. The films were prepared using four different water soluble polymers in various proportions and combinations using propylene glycol as plasticizers. Total five formulations were developed and evaluated for the various physicochemical characteristics namely mass uniformity, thickness, folding endurance, density, surface pH, swelling index, disintegration time, content uniformity, in vitro release profile, percent moisture absorption and loss and ex vivo mucoadhesion time. Data of every parameter were taken in triplicate. Results of film thickness, mass, density and swelling index of medicated films of LS were found with relatively low standard deviation along with high folding endurance (>300). The surface pH of all films approached to the salivary fluid pH range (6.1~7.0). Disintegration time and content uniformity complied with standard for all formulations. Among the total five formulations, F-2 and F-5 followed first order release and F-1 and F-4 followed Higuchi release and F-5 followed zero order and hixon-crowell release. The residence time for mucoadhesion of the tested films ranged between 1 to 5 minutes. Percent moisture absorption and loss study revealed the excellent stability of the films in dried conditions and relatively low standard deviation indicated the stability also in humid conditions. Bangladesh Pharmaceutical Journal 20(1): 64-70, 2017